Regular Consumption of Sauerkraut and Its Effect on Human Health: A Bibliometric Analysis. Issue 6 (November 2014) - Raak, Christa; Ostermann, Thomas; Boehm, Katja; Molsberger, Friedrich
Background: Sauerkraut is one of the most common and oldest forms of preserving cabbage and can be traced back as a food source to the 4th century BC. It contains a large quantity of lactic acid and tyramines, as well as vitamins and minerals, and has few calories. Objective: We aimed to provide an overview regarding the evidence of the effects of sauerkraut on human health by means of a bibliometric analysis. Methodology: Electronic databases (Medline, AMED, CamBase, CamQuest, the Cochrane Central Register of Controlled Trials, the Database of Abstracts of Reviews of Effects, the Cochrane Database of Systematic Reviews, EMBASE, the Karger-Publisher and the Thieme-Publisher databases) were searched from their inception until September 2012. Results: The search revealed 139 publications ranging over a 90-year period from 1921 to 2012. The majority of publications originated from Europe (48.6%), followed by the United States (30.7%) and Asia (10%). More than half of the research (56.8%) focused on food analysis, and 23.7% evaluated the impact of sauerkraut on health, including risk factors or digestive well-being. Direct research in humans was almost constant over time at about 11.5%. The studies found that sauerkraut induced inflammation locally, but repeated intake may result in diarrhea. Some studies pointed out anticarcinogenic effects of sauerkraut, while others concentrated on the interaction with monoamine oxidase inhibitors (MAOIs). Discussion: Sauerkraut, one of the oldest traditional foods, has a variety of beneficial effects on human health. However, unwanted effects such as intolerance reactions must be considered when dealing with sauerkraut as a functional food.